Menstrual Culture and Belief Systems: Understanding Traditional Perspectives and Changing Attitudes - Bhandari, Khimananda; Giri, Surendra; Belbase, Narayan (NPRC Journal of Multidisciplinary Research, 2025)
Background: Menstrual culture in Nepal is deeply rooted in traditional beliefs, particularly among adolescent girls. These beliefs often impact girls' education and social participation. This study examines menstrual culture and related attitudes among schoolgirls in Lumbini Province, focusing on traditional norms and shifting perceptions across social groups.Methods: A descriptive cross-sectional research design was employed among 400 menstruating girls from Grades 9 and 10 in 20 government secondary schools in Rupandehi and Kapilvastu districts. A multi-stage random sampling technique was used. Data were collected through a structured questionnaire and analyzed using IBM SPSS version 25.Results: The study found that 69.3% of participants perceived menstruation as a culturally significant phenomenon, primarily viewing it as a state of ritual impurity that required adherence to restrictions such as avoiding kitchens, temples, and public gatherings. The prevalence of such cultural beliefs was highest among Muslim girls (87.8%), followed by Hindu girls (68.3%), and lowest among Buddhist girls (14.3%). A significant correlation was observed between the father’s level of education and occupation with girls' attitudes—those with highly educated fathers were less likely to follow traditional menstrual norms.Conclusion: The findings underscore the enduring influence of cultural beliefs on menstrual attitudes, particularly among specific religious groups. However, increasing parental education, especially fathers’, plays a critical role in challenging traditional practices and promoting healthier perspectives on menstruation.Novelty: This study uniquely integrates socio-cultural dimensions with feminist and social justice theories, emphasizing the need for menstrual education and advocacy. It contributes valuable insights for developing culturally responsive interventions aimed at promoting gender equity in education.